Special operations from a small state perspective future security challenges - Eriksson, Gunilla; Pettersson, Ulrica (New Security Challenges, 2017)
This book offers different perspectives on the utilization and development of special operations forces (SOF) in small states. Across the chapters, the authors argue that small states can use and develop this very unique capability both at a tactical and operational level, but also as a strategic instrument in the modern complex security environment.